Program Implementation of Option B– at a President’s Emergency Plan for AIDS Relief-Supported HIV Clinic Improves Clinical Indicators But Not Retention in Care in Mbarara, Uganda - Miller, Kathleen; Muyindike, Winnie; Matthews, Lynn T.; Kanyesigye, Michael; Siedner, Mark J. (AIDS patient care and STDs, 2017)
2013 WHO guidelines for prevention of mother to child transmission recommend combination antiretroviral therapy (ART) for all pregnant women, regardless of CD4 count (Option B/B+). We conducted a retrospective analysis of data from a government-operated HIV clinic in Mbarara, Uganda before and after implementation of Option B+ to assess the impact on retention in care. We limited our analysis to women not on ART at the time of their first reported pregnancy with CD4 count >350. We fit regression models to estimate relationships between calendar period (Option A vs. Option B+) and the primary outcome of interest, retention in care. One thousand and sixty-two women were included in the analysis. Women were more likely to start ART within 6 months of pregnancy in the Option B+ period (68% vs. 7%, p < 0.0001) and had significantly greater increases in CD4 count 1 year after pregnancy (+172 vs. -5 cells, p < 0.001). However, there was no difference in the proportion of women retained in care 1 year after pregnancy (73% vs. 70%, p = 0.34). In models adjusted for age, distance to clinic, marital status, and CD4 count, Option B+ was associated with a non-significant 30% increased odds of retention in care at 1 year [adjusted odds ratio (AOR) = 1.30, 95% CI 0.98–1.73, p = 0.06]. After transition to an Option B+ program, pregnant women with CD4 count >350 were more likely to initiate combination therapy; however, interventions to mitigate losses from HIV care during pregnancy are needed to improve the health of women, children, and families.
Keywords: PMTCT; Pregnancy; Retention in care